2005
DOI: 10.1097/01.mlg.0000172196.76865.a1
|View full text |Cite
|
Sign up to set email alerts
|

Jugular Foramen Schwannomas: Diagnosis, Management, and Outcomes

Abstract: Jugular foramen schwannomas can be successfully diagnosed preoperatively with computed tomography and magnetic resonance imaging. These tumors can be successfully managed with surgery and low morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 8 publications
2
61
0
3
Order By: Relevance
“…The frequency of this type has varied from 8.6% to 50% of jugular foramen schwannomas in different series. 8,19,26,30,31,40 The origin, radiological characteristics, and pathological behavior of jugular foramen schwannoma have been reviewed elsewhere. 5,8,18,26,31,36 In the nonpathological jugular foramen, CNs IX-XI course superomedial to the jugular bulb.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of this type has varied from 8.6% to 50% of jugular foramen schwannomas in different series. 8,19,26,30,31,40 The origin, radiological characteristics, and pathological behavior of jugular foramen schwannoma have been reviewed elsewhere. 5,8,18,26,31,36 In the nonpathological jugular foramen, CNs IX-XI course superomedial to the jugular bulb.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer than 200 cases of schwannomas arising from the jugular foramen have been reported in the literature, a testament to the rarity of this tumor. 25,29,41,53,59,65,71,74 Experience has shown that the traditional suboccipital and transmastoid approaches do not provide adequate exposure of these lesions. Understanding and utilizing advanced skull base surgery techniques and concepts is essential for adequate resection of these tumors with CN preservation.…”
mentioning
confidence: 99%
“…It is believed that the diagnosis and nerve origin can be determined by the initial symptoms and the grade of dysfunction of the nerve, especially when compared with adjacent nerves. This connection gives rise to the classic descriptions of the different syndromes affecting the lower cranial nerves 2,5,8,9 including descriptions by Vernet (involvement of the ninth, 10th, and 11th cranial nerves), Schmidt (the 10th and 11 th nerve), Collet-Sicard (9th, 10 th , 11th and 12th nerves), Jackson (the 10th, 11th, and 12th nerves), and Tapia (the 10th and 11 th , 12th nerves and symphathetic), Villeret (9 th ,10 th ,12 th and symphathetic) as well as a combination of these syndromes. Cases in the study can be named as Collet-Sicard plus VIII nerve syndrome!…”
Section: Discussionmentioning
confidence: 90%
“…The early symptoms of tumors originated in the jugular foramen are, in most cases, conductive hearing loss and tinnitus. Other lesions may cause paralysis of the lower cranial pairs as a first symptom 4 1,2,5,8 . It is believed that the diagnosis and nerve origin can be determined by the initial symptoms and the grade of dysfunction of the nerve, especially when compared with adjacent nerves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation